Pengaruh Job Embededdess Terhadap Kinerja Dengan Career Barriers Sebagai Moderasi (Studi pada Karyawan PT Madu Baru Yogyakarta) - Subkhi, Zainal Agus; Danupranata, Gita (Jurnal Manajemen Bisnis, 2016)
This research is aimed to identify the influence if job embededdness toward performance of employee with career barriers as variable of moderation. The information that was obtained from this research is very important for the company as the consideration to apply better Occuptaional Health and Safety for the employee. Subject of this research is the employees of PT. Madu Baru Yogyakarta. The sampling was taken by using purposive sampling,survey as the method of this research, and through that method this research gathered 100 respondents. SPSS was used to analyze data.The result of this research shows that job embededdness has positive impact to work performance and career carriers hasn’t affect the relation of job embededdness toward work performance.